Relationship between Postpartum Maternal Characteristics and Fatigue - Nurul Rahmawati; Misrawati Misrawati; Arneliwati Arneliwati (Journal of Education Technology Information Social Sciences and Health, 2024)
The most general physical health problem which occurs on postpartum mother is fatigue. Fatigue is a common ongoing condition experienced by postpartum women after childbirth. Symptoms of fatigue occur due to physical and psychological adjustments after childbirth. Fatigue during postpartum period are influenced by various factors included the demography factor. This research was conducted in the working area of Puskesmas Umban Sari Pekanbaru City. This research aimed to find out the correlation between the characteristics of postpartum mother towards fatigue. This research employed correlation method. The research samples were 66 respondents that were selected based on the inclusion criteria by using purposive sampling technique. The research used Postpartum Fatigue Scale. The analysis used was bivariate analysis by using chi-square test. The research result showed that there was a correlation between the mother’s age, latest education and occupation on postpartum fatigue.